Cross-Jurisdictional Law Against Cybercrime Using Private Blockchain in Global Supply Chain: A Case Study of The Food Industry - Wahyu Beny Mukti Setiyawan (Indonesian Cyber Law Review, 2026)
This study examines the cross-jurisdictional legal challenges in addressing cybercrime involving private blockchain technology in the global food supply chain. The research aims to identify cybersecurity risks, evaluate the adequacy of national and international regulations, and analyze mitigation strategies implemented by companies. A qualitative approach with a case study design was used, involving in-depth interviews with company managers, IT security teams, and regulators, as well as observations of blockchain implementation and documentation analysis. The findings indicate that private blockchains, while improving traceability and transparency, remain vulnerable to internal threats, malware, phishing, and system vulnerabilities. Legal challenges include overlapping jurisdictions, regulatory differences, and complex extradition processes, which hinder timely law enforcement. Companies adopt comprehensive mitigation strategies, including role-based access control, secure smart contracts, encryption, and collaboration with international regulators. The study concludes that an integrative approach combining technological safeguards, internal governance, and cross-jurisdictional legal coordination is critical to ensuring data integrity, regulatory compliance, and the resilience of global food supply chains to cyberthreats. This research contributes to understanding the intersection of blockchain technology, cybersecurity, and international law in the context of global trade.